2015
DOI: 10.2340/00015555-1981
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatisation, Avoidance Behaviour and Difficulties in Coping are Common Among Adult Patients with Vitiligo

Abstract: Vitiligo is a non-contagious skin disorder with loss of pigmentation, often impairing patients' well-being. This study used Dermatology Life Quality Index (DLQI), Adjustment to Chronic Skin Disorders Questionnaire (ACS), Beck Depression Inventory (BDI) and additional questions to explore quality of life (QoL), coping, depression and stigmatisation and included 96 patients with vitiligo and 23 controls. Stigmatisation was common: 87/96 patients (90%) reported questions/approaches, 23/96 (24%) experienced nasty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 59 publications
9
67
0
7
Order By: Relevance
“…Low levels of anxiety detected in children might be related to low levels of parental anxiety. As a condition that would possibly disrupt the fantasy of the idealized child, the child might be affected too, in case of insufficient adaptive mechanisms and the probability of parents reflecting their psychological distress on their children [35,38,78]. Our findings of parental anxiety levels not being higher than those in the control group might have created a positive effect such as moderate levels of anxiety in children and medium levels of vitiligo severity.…”
Section: Discussionmentioning
confidence: 64%
“…Low levels of anxiety detected in children might be related to low levels of parental anxiety. As a condition that would possibly disrupt the fantasy of the idealized child, the child might be affected too, in case of insufficient adaptive mechanisms and the probability of parents reflecting their psychological distress on their children [35,38,78]. Our findings of parental anxiety levels not being higher than those in the control group might have created a positive effect such as moderate levels of anxiety in children and medium levels of vitiligo severity.…”
Section: Discussionmentioning
confidence: 64%
“…When the studies assessed the prevalence of depressive symptoms among patients with vitiligo based on self‐reported questionnaires, the pooled prevalence of depressive symptoms was 0·34 (95% CI 0·25–0·42; P < 0·001) (Fig. c).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple observational studies have suggested an epidemiological link between vitiligo and psychiatric morbidity such as depression . However, other studies have failed to establish such a relationship . While most studies evaluated depressive symptoms using validated psychometric tests, a few defined depression clinically based on the criteria outlined in the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM‐IV).…”
mentioning
confidence: 99%
“…(Kruger and Schallreuter, 2014;Porter et al, 1987;Sukan and Maner, 2007) Moreover, studies conducted in several countries have shown that vitiligo has a major negative impact on patients' sexuality. (Parsad et al, 2003a;Porter et al, 1979;Sukan and Maner, 2007) Disappointingly, in a survey conducted by the Vitiligo Society UK, a majority of participants admit to obtaining information on vitiligo from non-medical sources.…”
Section: Discussionmentioning
confidence: 98%